The Effects of Hand Bath on the Autonomic and Central Nervous Systems - Nishijo, Hisao; Nakano, Hajime; Aitake, Michiyo; Hori, Etsuro (Japanese Journal of Nursing Art and Science, 2020)
The aim of this study is to clarify the effects of hand baths on the autonomic and nervous systems. For that, we divided subjects into two groups, a hyper-sympathetic tonus group and a hyper-parasympathetic tonus group. Two measurement paradigms were used : Subjects’ autonomic reaction to hand baths was measured using heart rate variability and the central reaction of the frontal lobe was measured using Near-Infrared Spectroscopy (NIRS). In total 20 subjects participated. The experimental conditions included both a hand bath with 38℃ water for 5 min and a naïve control. Results indicated that in the hyper-sympathetic tonus group the hand bath reduced sympathetic activity and increased both parasympathetic activity and subjective feelings of relaxation. On the other hand, in the hyper-parasympathetic tonus group the hand bath increased sympathetic activity, reduced parasympathetic activity, activated the frontal lobe and activated vitality. These findings indicate that hand baths help to balance the autonomic nervous system and induce positive subjective feelings.